Correlação entre fato e decisão no processo penal e no processo administrativo tributário - Campilongo, Paulo Antonio Fernandes (2012)
This research aims to carry out the confrontation between the tax administrative procedure, in particular regarding the correlation between the proceeding fact and the decision to be produced in each of those procedural modalities. Facing this analysis, it intends to verify whether the informant principles of the criminal process can be imported, subsidiarily, to the tax administrative procedure, without any communication rumor, so as to authorize the tax release review by the administrative authorities in the exercise of atypical trial activities. To do so, it resorts, under the scientific-theoretical approach, of both the logicalsemantic constructivism and the theory of autopoietic systems, in order to achieve an approximation of those theories and, thus, better understand how the syntactical closure and the semantic and pragmatic opening of the legal systems would occur, as well as the operational closure and the cognitive opening, defended by the mentioned theories. This provides the understanding and reasoning about how the communication operations in the legal system occur, how and at what time the legal facts enter the system and how important is the process in terms of legal safety, for its legitimacy. By taking the moment in time analysis of the insertion of the legal criminal fact and the tax legal fact in the legal system, as well as the legitimate authorities to enter them in a relevant language, the study herein tries to prove that the subsidiary application of the institutes of the amendment or libel change in criminal proceedings do not have the same connotation as the release review by mistake in fact or error straight of law in the course of the tax administrative procedure